HUBUNGAN STATUS IMUNISASI BCG DENGAN MORTALITAS DAN DERAJAT SEVERITAS MENINGITIS TUBERKULOSIS ANAK DI RSUP DR. M. DJAMIL PADANG PERIODE 2018 – 2021 - Nixon, Poety Elberta Husna; Lestari, Rahmi; Intan, Shinta Ayu; Amelin, Fitrisia; Ermayanti, Sabrina; Adrial, Adrial (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Objective: This study aims to determine the relationship between BCG immunization status with mortality and severity of TB meningitis in children at RSUP Dr. M. Djamil Padang. Method: This study used a cross-sectional design in children with TB meningitis and used the Kolmogorov-Smirnov and Chi-Square statistical tests. Sampling using total sampling technique with a total sample of 58 people. Data obtained from the medical records of RSUP Dr. M. Djamil Padang in 2018 – 2021. Result: This study shows that most pediatric TB meningitis patients with the condition are women (53%), aged 0-4 years (48%), good nutritional status (40%), not in direct contact with TB patients (74%), received BCG immunization (55%), severe degree (59%), and alive (76%). There is a relationship between BCG immunization status and degree of severity (p=0.046) and mortality (p=0.047) of pediatric TB meningitis patients at RSUP Dr. M. Djamil Padang in 2018 – 2021. Conclusion: The conclusion of this study is that there is a relationship between BCG immunization status and the degree of severity and mortality of TB meningitis in children at RSUP Dr. M. Djamil Padang in 2018 – 2021.